Analisis Kesulitan Membaca Permulaan pada Siswa Sekolah Dasar - Pipit Pratiwi; Cicih Wiarsih (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Early reading is an important basic skill for students. Early reading is the main foundation that influences subsequent reading ability. This study aims to describe the difficulties of early reading in second grade students at SDN 1 Kedungwuluh, the factors that cause difficulties in early reading, and the efforts made by teachers to overcome difficulties in early reading. The research method used is qualitative with a case study approach. The sample consists of 18 students in Class II B of SDN 1 Kedungwuluh, selected using purposive sampling. Data collection was conducted through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The results of the study indicate that: (1) six students experienced early reading difficulties, namely (a) difficulty recognizing letters, (b) omission or substitution, (c) difficulty spelling, (d) adding letters, and (e) reversing letters; (2) the factors causing reading difficulties were (1) psychological factors, (2) family environment factors, and (3) to overcome early reading difficulties, the following measures were taken: (a) teachers providing reading guidance programs, (b) using the SAS method. This study concluded that the involvement of teachers, parents, and students is necessary through the implementation of appropriate strategies and continuous support.Membaca permulaan merupakan keterampilan dasar yang penting bagi siswa. Membaca permulaan menjadi fondasi utama yang memengaruhi kemampuan membaca selanjutnya. Penelitian ini bertujuan untuk mendeskripsikan kesulitan membaca permulaan pada siswa kelas II B SDN 1 Kedungwuluh, faktor penyebab yang mempengaruhi kesulitan membaca permulaan, dan upaya yang dilakukan guru dalam mengatasi kesulitan membaca permulaan. Metode penelitian ini adalah kualitatif dengan jenis studi kasus. Sampel pada penelitian ini adalah sswa kelas II B SDN 1 Kedungwuluh yang berjumlah 6 siswa dengan teknik pengambilan sampel menggunakan teknik purposive sampling. Pengumpulan data dengan menggunakan teknik observasi, wawancara dan dokumentasi, selanjutnya dianalisis menggunakan model Miles and Huberman. Berdasarkan hasil penelitian menunjukkan bahwa: siswa mengalami kesulitan membaca permulaan, yaitu kurang mengenali huruf, penghilangan atau penggantian, kesulitan mengeja, penambahan huruf dan pembalikkan huruf; faktor penyebab kesulitan membaca yaitu faktor psikologis dan faktor lingkungan keluarga; untuk mengatasi kesulitan membaca permulaan antara lain: guru memberikan program bimbingan membaca, menggunakan metode SAS. Penelitian ini menyimpulkan memerlukan keterlibatan guru, orang tua, dan siswa melalui penerapan strategi yang tepat serta dukungan yang terus-menerus.